Two-Dimensional Semiconductor Materials - Chen, Jifan (Transactions on Computer Science and Intelligent Systems Research, 2024)
Compared to traditional three-dimensional semiconductors, two-dimensional semiconductors exhibit a multitude of distinctive electronic transport and optical properties at the nanoscale. These exceptional properties, such as enhanced electron mobility, direct bandgap, and quantum confinement effects, offer groundbreaking possibilities for the development of novel nanoelectronics and optoelectronics devices. The unique characteristics of 2D materials enable the creation of ultra-thin, flexible, and highly efficient devices that can perform tasks previously unattainable with conventional materials. This opens up new avenues in various fields, including high-speed transistors, advanced photodetectors, and next-generation light-emitting diodes (LEDs), thereby revolutionizing the landscape of modern technology. Through the design of layered structures, two-dimensional semiconductors can achieve controlled quantum confinement effects in the vertical direction, demonstrating excellent charge carrier transport properties and optical characteristics. For instance, graphene is one of the most well-known two-dimensional semiconductors. It possesses high electron mobility and exceptional mechanical strength, making it suitable for flexible electronics and sensor technologies. In addition to graphene, materials such as molybdenum disulfide and tungsten disulfide also exhibit unique optoelectronic properties that can be utilized in photodetectors and photovoltaic devices. Research on these materials not only contributes to a deeper understanding of electronic behavior at the nanoscale but also has the potential to drive further miniaturization and performance enhancement of semiconductor devices. Overall, two-dimensional semiconductors represent a frontier research direction in the field of semiconductor materials, offering promising opportunities and challenges for the future development of nanoelectronics and optoelectronics.